Odpowiedź :
a)
[tex]1 \frac{5}{6} \div 3 \frac{2}{3} \times 1 \frac{1}{7} = \frac{11}{6} \div \frac{11}{3} \times \frac{8}{7} = \frac{11}{6} \times \frac{3}{11} \times \frac{8}{7} = \frac{8}{14} = \frac{4}{7} [/tex]
b)
[tex] {( \frac{1}{2}) }^{3} \times 2 \frac{2}{3} \div 1 \frac{1}{6} = \frac{1}{8} \times \frac{8}{3} \times \frac{6}{7} = \frac{2}{7} [/tex]
c)
[tex]1 \frac{1}{4} \times 6 - 3 \div 1 \frac{1}{5} = \frac{5}{4} \times 6 - 3 \times \frac{5}{6} = \frac{15}{2} - \frac{5}{2} = \frac{10}{2} = 5[/tex]
d)
[tex](4 \frac{3}{8} - 1 \frac{2}{3} ) \div 3 \frac{3}{4} = ( \frac{35}{8} - \frac{5}{3} ) \div \frac{15}{4} = ( \frac{105}{24} - \frac{40}{24}) \times \frac{4}{15} = \frac{65}{24} \times \frac{4}{15} = \frac{13}{18} [/tex]
e)
[tex]2 \frac{1}{5} - 1 \frac{1}{6} \div 2 \frac{1}{3} = \frac{11}{5} - \frac{7}{6} \times \frac{3}{7} = \frac{11}{5} - \frac{1}{2} = \frac{22}{10} - \frac{5}{10} = \frac{17}{10} = 1 \frac{7}{10} [/tex]
Odpowiedź:
a) 1 i 5/6 : 3 i 2/3 *1 i 1/7= 11/6: 11/3*8/7= 11/6*3/11*8/7( skracamy 11 i 11 przez 11 ,
oraz 3 i 6 przez 3)= 1/2*8/7( skracamy 8 i 2 przez 2)= 4/7
b) ( 1/2)³ *2 i 2/3 : 1 i 1/6= 1/8* 8/3: 7/6= 1/8*8/3*6/7( skracamy 8 i 8 przez 8,
oraz 3 i 6 przez 3)= 2/7
c) 1 i 1/4 *6 -3: 1 i 1/5= 5/4*6 - 3: 6/5( skracamy 4 i 6 przez 2)=5/2*3 -3*5/6(
skracamy 3 i 6 przez 3)= 15/2 - 5/2 = 10/2=5
d) ( 4 i 3/8 -1 2/3 ) : 3 i 3/4= ( 4 i 9/24- 1 i 16/24) :3 i 3/4=
=( 3 i 33/24-1 i 16/24):3 i 3/4= 2 i 17/24 : 3 i 3/4= 65/24 : 15/4=
= 65/24* 4/15( skracamy 65 i 15 przez 5, oraz 24 i 4 przez 4)=
= 13/6*1/3 = 13/18
e) 2 i 1/5 - 1 i 1/6 : 2 i 1/3= 2 i 1/5- 7/6: 7/3= 2 i 1/5- 7/6*3/7( skracamy 7 i 7
przez 7, oraz 3 i 6 przez 3)= 2 i 1/5- 1/2= 2 i 2/10-5/10=
=1 i 12/10-5/10= 1 i 7/10
Szczegółowe wyjaśnienie: